DIRECTIONS OF IMPROVEMENT OF PUBLIC ADMINISTRATION IN THE FIELD OF EDUCATION AT THE REGIONAL LEVEL - Sierkova , Nadiya (Theory and Practice of Public Administration, 2019)
The article covers the issues of public administration in the field of education at the regional leveland discusses the improvement of the structure of training by levels and specialties in accordance with the needs of the economy. The opinion is expressed that the needs of the economy in trained professionals have been determined as well as continue to be determined by the education system itself, at present they continue to be determined by the educational institutions themselves and this problem is not practically solved at the system level.In the modern economy, man becomes the center of recovery processes. The evidence of that is a growth of the importance of human capital which is formed under the influence of the education system and educational activities. It is education that affects the development of natural abilities of the person to work, facilitates the moral and spiritual education of pupils, students, listeners.Recently, the category of sustainable development has been widely used in the economic literature.The experience of the developed countries regarding the further socio-economic development of the state shows that there are fundamental foundations for sustainable development.Those could be education, the level of education and the educational potential of the nation,which are an important factor of the formation, safekeeping and strengthening of national security.The external subjects of the directions of improvement of education management system at regional level are state (regional) authorities as well as public structures. At the same time, education management is also considered as an important sociocultural function of government bodies, which defines a lot of perspectives of the development of society, and as a traditional mission of social structures. In the regions, the management of education is entrusted to the chairman of a branch body of executive power.The object of the direction of improvement of the management system is the sphere of education. This category carries a multi-aspect semantic meaning: on the one hand, it can be regarded as the sphere of life of the subjects and, on the other, as a socio-economic system designed to provide the living conditions of the subjects and at the same time meet the educational needs of man, society and the state. The sphere of education at the country and society level is the area of public life, its subsystem; the sphere of education at the regional level is a socio-economic subsystem, which is a branch of economy and a constituent element of the social structure of the territorial community.